Immigration, Unemployment and Wages: New Causality Evidence from the United Kingdom - Cigdem Börke Tunali; Jan Fidrmuc; Nauro F. Campos (Center for Economic Studies and ifo Institute (CESifo), 2017)
The vast literature on the effects of immigration on wages and employment is plagued by likely endogeneity and aggregation biases. Ours is among the first papers to address both of these issues by means of causality analysis and by accounting for human capital endowments. Our analysis confirms the previous finding of limited effect of immigration on unemployment and wages in aggregate analysis. We do find, however, evidence of distributional effects when accounting for human capital of non-migrants.
Keywords: F22; J21; J61; 330; immigration; unemployment; wages; UK; European Union